Biotechnological Agents for Patients With Tumor Necrosis Factor Receptor Associated Periodic Syndrome—Therapeutic Outcome and Predictors of Response: Real-Life Data From the AIDA Network - Vitale, Antonio; Obici, Laura; Cattalini, Marco; Lopalco, Giuseppe; Merlini, Giampaolo; Ricco, Nicola; Soriano, Alessandra; La Torre, Francesco; Verrecchia, Elena; Insalaco, Antonella; Dagna, Lorenzo; Jaber, Masen Abdel; et al. (Frontiers in Medicine, 2021)
Objective: to describe the role of biotechnological therapies in patients with tumor necrosis factor receptor associated periodic syndrome (TRAPS) and to identify any predictor of complete response. Methods: clinical, laboratory and therapeutic data from 44 Caucasian TRAPS patients treated with biologic agents were retrospectively collected in 16 Italian tertiary Centers. Results: a total of 55 biological courses with anakinra (n=26), canakinumab (n=16), anti-TNF-α agents (n=10) and tocilizumab (n=3) were analysed. A complete response was observed in 41 (74.5%) cases, a partial response in 9 (16.4%) cases and a treatment failure in 5 (9.1%) cases. The frequency of TRAPS exacerbations was 458.2 flare/100 patients-year during the 12 months prior to the start of biologic treatment and 65.7 flare/100 patients-years during the first 12 months of therapy (p<0.0001). The median duration of attacks was 5.00 (IQR=10.50) days at the start of biologics and 1.00 (IQR=0.00) days at the 12-month assessment (p<0.0001). Likewise, a significant reduction was observed in the Autoinflammatory Disease Activity Index during the study period (p<0.0001). A significant corticosteroid sparing effect was observed as early as the first 12 months of treatment both in the number of patients requiring corticosteroids (p=0.025) and in the dosages employed (p<0.0001). A significant reduction was identified in the erythrocyte sedimentation rate (p<0.0001), C reactive protein (p<0.0001), serum amyloid A (p<0.0001) and in the 24-hour proteinuria dosage during follow-up (p=0.001). A relapsing-remitting disease course (OR=0.027, C.I. 0.001-0.841, p=0.040) and the frequency of relapses at the start of biologics (OR=0.363, C.I. 0.301-0.953, p=0.034) were significantly associated with a complete response. No serious adverse events were observed. Conclusions: treatment with biologic agents is highly effective in controlling clinical and laboratory TRAPS manifestations. Patients with a relapsing-remitting course and a lower frequency of flares at the start of treatment show more likely a complete response to biologic agents.